Development of sand production prediction computer model - Samsuri, Ariffin; Sim, Soon Hin (2001)
During production, sand inflow from poorly consolidated reservoir will cause problems of wear, casing collapse and surface facility deterioration. However, if the sand control completion is used to minimize sand production risk, it may lead to high skins and resulting in large productivity loses. On the other hand, completion without sand control device may lead to sand production problems with economial loss and safety risks. The best way to assess the problem is prediction of sand production, which basically come from the perforation. Therefore, a two-dimensional numerical model will be developed to simulate and monitor the stability of perforation and predict when sand will be produced during production phase. In developing the perforation cavity stability prediction model, the rock is assumed to be isotropic and homogeneous with the pores completely filled with fluid.